Concurrent Design of Linear Control with Input Shaping for a Two-Link Flexible Manipulator Arm. Issue 14 (2018) - Newman, Daniel; Vaughan, Joshua
Abstract: Input shaping is an effective vibration control technique for flexible systems with known dynamic characteristics. However, due to its open-loop nature, it must be combined with a feedback controller to enable rejection of unknown disturbances. Although a number of researchers have demonstrated the effectiveness of combining input shaping and feedback control methods, performance gains can be made by cooperatively designing the feedback gains and input shaping sequence. This paper presents a preliminary investigation of such a control method on a two-link flexible manipulator. This formulation allows for energy-efficient point-to-point motion while simultaneously minimizing command-induced vibration. Simulations demonstrate the effectiveness of this preliminary work.